The Role of Public Integrity in Controlling Corruption - Mutiah, Adilah Sabrina; Gamayuni, Rindu Rika; Oktavia, Reni; Wulan, Diajeng Fitri (Jurnal Ekonomi Pembangunan, 2024)
This study aims to analyze the extent to which the Index of Public Integrity can be used to increase Perceived Corruption so that low and low-middle-income countries can form policies that will increase the country's ability to control corruption in the future. This study uses panel data from the Index of Public Integrity by ERCAS and the Corruption Perception Index by Transparency International in low and low-middle-income countries during 2016 – 2022. Regression analysis, t-test, and R-Square were done using EViews 9 software. Test results show Administrative Transparency, Online Services, Freedom of the Press, and Judicial Independence positively influence the Corruption Perception Index so that it can be used as a major consideration in formulating government policies and regulations to reduce corruption. Meanwhile, E-Citizenship has no influence and Budget Transparency has a negative relationship with Perceived Corruption because of the legal culture. This research can contribute a basis and consideration in preparing government policies aimed at controlling the level of corruption in a country.